ECMS 2018 Proceedings Edited by Lars Nolle, Alexandra Burger, Christoph Tholen, Jens Werner, Jens Wellhausen 2018
DOI: 10.7148/2018-0205
|View full text |Cite
|
Sign up to set email alerts
|

MATLAB Toolbox For Self-Tuning Predictive Control Of Time-Delayed Systems

Abstract: The designed MATLAB/SIMULINK Toolbox is dedicated to develop and design predictive Self-Tuning Control (STC) algorithm for the time-delayed systems. In practice, many processes can exhibit time-delay in their dynamic behavior, which is mainly caused by a time needed for transport of the energy, information, or mass. In lights of these facts, it is necessary to develop suitable algorithm and verify its correct dynamic behavior using simulation first, so this Toolbox can be used in advantage. This paper deals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, Garcia and Chua [24] proposed using a hybrid model composed of a gas and electric water heater for fast hot water supply responses while decreasing energy consumption and CO 2 emissions. Finally, Bobál et al [25,26] implemented a Smith predictor control approach for heat exchangers. However, the Smith predictor requires an accurate estimation of models and dead time; moreover, it is susceptible to the linearisation operating point and designed for fixed time delays.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Garcia and Chua [24] proposed using a hybrid model composed of a gas and electric water heater for fast hot water supply responses while decreasing energy consumption and CO 2 emissions. Finally, Bobál et al [25,26] implemented a Smith predictor control approach for heat exchangers. However, the Smith predictor requires an accurate estimation of models and dead time; moreover, it is susceptible to the linearisation operating point and designed for fixed time delays.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the control strategy significantly influences the quality system performance and thermal performance. In the work conducted by (Costa, Ferreira and Guilherme, 2016) Bobal et al (Bobal et al, 2013) (Holiš and Bobál, 2007) (Holiš and Bobál, 2015) (Bobál et al, 2012) and (Bobál et al, 2014) implemented their own Matlab and Simulink toolboxes taking into consideration a Smith predictor control approach combined with different control strategies, namely digital PID, digital pole assignment, and model predictive control applied to the control of heat exchangers. Smith's predictor is a self-tuning method, and its main objective is to include time delay in the controller (Hang, Lim and Chong, 1989).…”
Section: Introductionmentioning
confidence: 99%